Student Satisfaction with University Facilities Using Cross Tabulation Analysis, Correspondence Analysis and Analytic Hierarchy Process - Abdul Aziz, Muhammad Aiman; Che Him, Norziha; Abd Latif, Noor Azliza; Yusof, Yusliandy (Enhanced Knowledge in Sciences and Technology, 2026)
University student satisfaction with facilities is a significant factor in determining the overall student learning process and welfare. This study investigates undergraduate student satisfaction with the facilities offered by Malaysian public universities and identifies the facilities that are most important in achieving overall satisfaction. This study employed secondary data obtained from Mendeley Data, which encompassed 280 respondents from the diploma, undergraduate, and postgraduate levels. To investigate the relationship between demographic features and the degree of satisfaction, the Cross Tabulation Analysis was applied. Correspondence Analysis was then used to examine the pattern of association between the categories of satisfaction and facilities of the university, and the Analytic Hierarchy Process was used to rank facilities in accordance with their relative significance in overall satisfaction. The results indicate significant associations between demographic characteristics and student satisfaction levels when the p-values < 0.05, suggesting that perceptions of university facilities vary substantially across gender, religion, age, and level of study. It also shows distinct association patterns between university facilities and satisfaction categories, with academic and support facilities clustering closer to high satisfaction, while infrastructure-related facilities are more strongly associated with lower satisfaction levels. AHP findings reveal that Bursary has the highest priority (0.2187) compared to Welfare, Health Centre, Islamic Centre and Library for Academic and Student Support Facilities. For Campus Infrastructure and Utilities, Wireless Internet has the most weight (0.2268) followed by Parking Lot, Toilet, Cleanliness and Cafeteria, while for Student Life and Campus Services, Transportation Centre has the highest weight (0.2815) followed by Auto-teller Machine, Sports Centre and Residential College. In conclusion, this study has provided a useful implication for university administrators in terms of setting priorities for improvement of facilities and encouraging data-driven decision-making to improve campus life for students. Future research may extend this study by conducting primary surveys with larger sample sizes to improve the generalisability of findings on student satisfaction with university facilities.